Targeting heat shock proteins 90 and 70: A promising remedy for both autoimmune bullous diseases and COVID-19 - Kasperkiewicz, Michael; Tukaj, Stefan (Frontiers in Immunology, 2022)
Heat shock proteins (Hsps), including Hsp90 and Hsp70, are intra- and extracellular molecules implicated in cellular homeostasis and immune processes and are induced by cell stress such as inflammation and infection. Autoimmune bullous disorders (AIBDs) and COVID-19 represent potentially life-threatening inflammatory and infectious diseases, respectively. A significant portion of AIBDs remain refractory to currently available immunosuppressive therapies, which may represent a risk factor for COVID-19 and suffer from treatment side-effects. Despite advances in vaccination, there is still a need to develop new therapeutic approaches targeting SARS-CoV-2, especially considering vaccine hesitancy, logistical distribution challenges, and breakthrough infections. In this mini review, we briefly summarize the role of targeting Hsp90/70 as a promising double-edged sword in the therapy of AIBDs and COVID-19.